ANALISIS PROBLEM STRUCTURING SECARA BERTINGKAT PROGRAM REVITALISASI POSYANDU DI KECAMATAN WONOKERTO KABUPATEN PEKALONGAN - Yuniarti .; Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
The purpose of this study is to arrange the structuring problems of Posyandu revitalization program. The  method  of  the  study  is  stepping  qualitative  analysis  method;  problems  finding,  problems grouping, problems specification, and problems understanding. The method of collecting data used is  hierarchy  method  in  each  problem.  The  research  informant  is  the  head  of  Wonokerto  Public Health Center and Posyandu representative in random sampling. The units of analysis are the time series  of  Posyandu  in  the  last  three  years,  the  result  of  the  interview  with  the  informant,  and  the result  of  observation  in  Posyandu  services.  The  result  of  the  study  shows  that  the  structuring revitalization  program  consists  of  three  aspects;  input,  process, and  out  put.  In  the  aspect  of  input shows that the number of Posyandu representative is increasing by the integration of representative groups, almost all Posyandu have facilities and adequate amount of medicine to support the services, all  of  Posyandu representative have been trained  but  the  activeness is  still law, the  public funding can support the work of Posyandu, the other support by Universities, and PKK participation. In the aspect  of  process  shows  that  the  number  of  representative  trainings  has  increased,  there  are  only basic services and there is no additional service, the involvement of public is not significant but the number of visit has increased, and the survey of children growth is held by Posyandu representative. The aspect of out put shows that the increasing of diseases problems finding by the house visitation, such as; ISPA, mal-nutrient, and hydrocephalus.Key words: Stepped Structuring Problems, Posyandu Revitalization Problems